Bringing regenerative medicines to the clinic: the future for regulation and reimbursement. (October 2015) - Bubela, Tania; McCabe, Christopher; Archibald, Peter; Atkins, Harold; Bradshaw, Steven; Kefalas, Panos; Mujoomdar, Michelle; Packer, Claire; Piret, James; Raxworthy, Mike; Soares, Marta; Viswanathan, Sowmya
Significant investments in regenerative medicine necessitate discussion to align evidentiary requirements and decision-making considerations from regulatory, health system payer and developer perspectives. Only with coordinated efforts will the potential of regenerative medicine be realized. We report on discussions from two workshops sponsored by NICE, University of Alberta, Cell Therapy Catapult and Centre for Commercialization of Regenerative Medicine. We discuss methods to support the assessment of value for regenerative medicine products and services and the synergies that exist between market authorization and reimbursement regulations and practices. We discuss the convergence in novel adaptive licensing practices that may promote the development and adoption of novel therapeutics that meet the needs of healthcare payers.